Long-Term Response to Sunitinib Treatment in Metastatic Renal Cell Carcinoma: A Pooled Analysis of Clinical Trials - Tannir, Nizar M. (Clin Genitourin Cancer, 2017)
BACKGROUND: We characterized clinical outcomes of patients with metastatic renal cell carcinoma (mRCC) treated with sunitinib who were long-term responders (LTRs), defined as patients having progression-free survival (PFS) >18 months. PATIENTS AND METHODS: A retrospective analysis of data from 5714 patients with mRCC treated with sunitinib in eight phase II/III clinical trials and the expanded access program. Duration on-study and objective response rate (ORR) were compared between LTRs and patients with PFS ≤18 months (“others”). PFS and overall survival (OS) were summarized using Kaplan–Meier methodology. RESULTS: Overall, 898 (15.7%) patients achieved a long-term response and 4816 (84.3%) patients didn’t achieve long-term response. The median (range) duration on-study was 28.6 (16.8–70.7) months in LTRs and 5.5 (0–68.8) months in others. ORR was 51% in LTRs versus 14% in others (P < .0001). Median PFS in LTRs was 32.11 months and median OS was not reached. LTRs had higher percentage of early tumor shrinkage ≥10% at the first scan (67.1% vs. 51.2%; P=.0018) and greater median maximum on-study tumor shrinkage from baseline (−56.9 vs.−27.1; P<.0001) versus others. White race, Eastern Cooperative Oncology Group performance status 0, time from diagnosis to treatment ≥1 year, clear-cell histology, no liver metastasis, lactate dehydrogenase ≤1.5 upper limit of normal (ULN), corrected calcium ≤10 mg/dL, hemoglobin >lower limit of normal, platelets ≤ULN, BMI ≥25 kg/m(2), and low neutrophil-to-lymphocyte ratio were associated with LTR. CONCLUSION: A subset of patients with mRCC treated with sunitinib achieved long-term response. LTRs had improved ORR, PFS, and OS. TRIALS REGISTRATION NUMBERS: , , , , , , , ,